Rogue cops among rogues trolls and trolling in social networking sites - Escartin, Maria Corinna Priscila D. (2015)
Contents reflecting sarcasm, insults and provocation have been known to bombard online fora, Facebook pages, and other social networking sites. The rise of "rolls" or individuals who, for personal amusement, post online comments or content that tend to be disruptive, aggressive or inflammatory, in order to provoke a reaction from an audience, accompanied the popularity of social networking.

This study investigates what motivates online users to engage in "trolling". It looks into the characteristics and traits of the "troll" and the "trolled" as well as the possible factors that allow for such behavior to exist.
To get insights into the practice, the experiences of selected youths from ages 15 to 30, who are frequent users of the Internet and social networking sites, were gathered through an open-ended questionnaire with follow-up questions via emails or online communication. The instrument asked about their awareness of trolling, engagement in the activity, what their pictures of trolls are, and what posts or online content are considered "troll-able".
The study found that in "trolling", the anonymity and temporary identity suspension online prevalent in some forms of computer-mediated communication, supports a venue for people to "unleash" certain impulses not appropriate in face-t-face interaction. This study also suggests that, ironically, trolling also serves as a form of online behavior regulation. Thus, trolling allows the testing and reinforcement of boundaries of proper online behavior. When further explored, it can reveal the deeper dimensions of social interaction that take place in social networking sites.
Keywords: Social networks; Social media; Online etiquette; Online trolling